Design thinking : n the act or practice of using your mind to consider design - Ambrose, Gavin, ....-; Harris, Paul, 1971- (Lausanne : Ava Academia, 2010)
Basics Design: Design Thinking is an introduction to the process of generating creative ideas and concepts used by designers in order to start the process that leads to a finished piece of work. This focus on ideas and methods favours a useable approach to design as a problem-solving activity. This is supported by practical work examples and case studies from leading contemporary design studios, accompanied by concise descriptions, technical expansions and diagrammatic visualisations. Basics Design: Design Thinking teaches the generation of ideas as a practical skill, vital to the creation of successful design.